Diamine Oxidase rs10156191 and rs2052129 Variants Are Associated With the Risk for Migraine. Issue 2 (22nd January 2015) - García‐Martín, Elena; Martínez, Carmen; Serrador, Mercedes; Alonso‐Navarro, Hortensia; Ayuso, Pedro; Navacerrada, Francisco; Agúndez, José A. G.; Jiménez‐Jiménez, Félix Javier
<x xml:space="preserve">Abstract</x> Background Histamine has been implicated in the pathogenesis of migraine. We investigated the possible association between functional single nucleotide polymorphisms (SNPs) in the diamine oxidase gene (DAO; chromosome 7q36.1, involved in histamine metabolism) and the risk for migraine. Methods We studied the frequency of the rs2052129, rs10156191, rs1049742, and rs1049793 genotypes and allelic variants in 197 patients with migraine and 245 healthy controls using a TaqMan‐based qPCR Assay. Results The DAO SNP rs10156191, which is related to decreased DAO enzyme activity, is associated with the risk of developing migraine, particularly in women. The odds ratio (OR) for the defect allele positivity is 1.61 (95% confidence interval 1.31‐2.37) for overall migraine patients and 2.08 (1.29‐3.36) for women suffering from migraine. The association was not influenced by confounders such as the age at onset, the presence of aura, positivity of alcohol as a triggering factor, positive family history of aura, or family history of allergy. Multiple regression analyses did not confirm association with the rest of genetic factors. Conclusion Our findings, which should be framed as hypothesis generating, suggest that DAO genotypes and allelic variants are associated with the risk for migraine in Caucasian Spanish people, especially in women.